ANALYSIS OF THE CONCENTRATION OF AGRICULTURAL EMPLOYMENT OF THE STATE OF PERNAMBUCO: 2000 -2014 - Lacerda, Talinny Nogueira; Universidade Federal Rural de Pernambuco (2017)
Even in front of structural changes in recent decades, the Região Nordeste economy still has a large number of workers bound to agriculture, in particular the Estado de Pernambuco. In this context, this paper aims to identify the concentration of the job on agricultural sector of the Estado de Pernambuco between the years 2000 to 2012. For this, the location quotient, the restructuring coefficient, the redistribution coefficient and the specialization coefficient was calculated with data from the Relação Anual de Informações Sociais (RAIS). The results indicated that there was no strong structural changes in the composition of agricultural employment between microregions. The employment in the regions showed low specialization and any changes in the distribution pattern. However, it was possible to identify regions with significant concentration of agricultural employment within of the Estado de Pernambuco.